UK Training in Oncology: The View From 'the Other Side'. Issue 4 (April 2019) - Frazer, R.; Pugsley, L.; Button, M.; Cleves, A.
Highlights: Transition from registrar to consultant is one of the most challenging stages in a doctors career. New consultants often feel unprepared for consultant life despite registrar training. Clinical and medical oncologists face similar challenges despite differences in training structure and curricula. Non clinical skills are the main challenges faced by new consultant oncologists in the early years.